2016
DOI: 10.1016/j.carbon.2016.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted preparation of electrospun carbon fiber/graphene electrodes for capacitive deionization: Importance and unique role of electrical conductivity

Abstract: The desalination performance of capacitive deionization (CDI) technology is governed by electrode material properties, such as specific surface area, pore size and structure, surface functional groups, electrode geometry, and electrical conductivity. However, few studies have been conducted regarding the impact of the electrical conductivity of electrode materials on the desalination performance of CDI. In this study, monolithic composite web electrodes are fabricated. These electrodes are composed of reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(41 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…[1] CDI has attracted academic and industrial attention as an ovel desalination process owing to its advantagessuch as high energyefficiency,environmental friendliness, and high water recovery. [1][2][3][4][5][6][7][8][9] The conventionalC DI cell concept [10] utilizesapair (or multiple pairs)o fn anoporous carbon electrodes separated by aspacertoprevent the electric short circuit and to provideaflow channel for feed water.T he most common CDI operation is constituted of two steps, namely,t he charging half-cycle (purification/electroadsorption) and discharging half-cycle (regeneration/electrodesorption) steps. [11] During the first step, the porous electrode pair is chargedb ya na pplied voltage, ands alt ions are electroadsorbed onto the oppositely charged electrode by electrical double-layer (EDL) formation at the interface of the porous electrode and water.T herefore, salt ions are immobilized from the aqueous feed solution.T he adsorbed ions are released from the electrodes in the discharging step, whichi so perated with reversed polarity or short circuit, resulting in aconcentrated effluent stream.…”
Section: Introductionmentioning
confidence: 99%
“…[1] CDI has attracted academic and industrial attention as an ovel desalination process owing to its advantagessuch as high energyefficiency,environmental friendliness, and high water recovery. [1][2][3][4][5][6][7][8][9] The conventionalC DI cell concept [10] utilizesapair (or multiple pairs)o fn anoporous carbon electrodes separated by aspacertoprevent the electric short circuit and to provideaflow channel for feed water.T he most common CDI operation is constituted of two steps, namely,t he charging half-cycle (purification/electroadsorption) and discharging half-cycle (regeneration/electrodesorption) steps. [11] During the first step, the porous electrode pair is chargedb ya na pplied voltage, ands alt ions are electroadsorbed onto the oppositely charged electrode by electrical double-layer (EDL) formation at the interface of the porous electrode and water.T herefore, salt ions are immobilized from the aqueous feed solution.T he adsorbed ions are released from the electrodes in the discharging step, whichi so perated with reversed polarity or short circuit, resulting in aconcentrated effluent stream.…”
Section: Introductionmentioning
confidence: 99%
“…Capacitive deionization (CDI) has risen over the years as a durable, energy efficient, and cost-effective electrochemical desalination technology [15][16][17][18][19][20][21][22]. In addition to recent developments in removing heavy metals using manganese oxides [23][24][25][26], the progresses in the field of CDI have been mainly made in expanding the application of porous carbons with good electrical conductivity and high specific surface area (SSA) [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The electrosorption capacity and stability of an electrode depend on its pore structure, surface area, and electrical conductivity of electrode [1][2][3][4][5][6]. These play a significant role in the improvement of electrical double-layer capacitance in a capacitive deionization (CDI) system.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, carbon materials like carbon nanofiber (CNF), carbon nanotubes (CNTs), graphene, and reticulated vitreous carbon (RVC) are used as electrode materials in a CDI system [7][8][9][10]. Wang et al have shown that the electrical conductivity of electrode materials plays a great role in the performance of a CDI system [6]. They prepared a monolithic composite electrode using reduced graphene oxide (rGO) and activated carbon nanofiber (aCNF) through an ultrasound-assisted electrospinning technique.…”
Section: Introductionmentioning
confidence: 99%